Students' opinion towards mathematics course in Mengubah Destini Anak Bangsa (MDAB) program / Suriyati Ujang, Syafiza Saila Samsudin and Nur Hidayah Masni Abdullah - Ujang, Suriyati; Samsudin, Syafiza Saila; Abdullah, Nur Hidayah Masni (2014)
Mengubah Destini Anak Bangsa (MDAB) Program is a program inspired by YAB Dato' Seri Najib Bin Razak, the Prime Minister of Malaysia. This program has been offered at Universiti Teknologi MARA since 2010. Through this program, students are enrolled in Pre-Diploma program. Passing the Pre-Diploma program will enable them to further their study to the diploma level. However, there are some issues involving the MOAB students. There are numbers of the students who did not achieve good results or fail in mathematics courses at diploma level. Thus, this study was conducted to look at the perception of the MDAB students towards Mathematics and the correlation between their perception and their mathematics' result. Sample for this research are first semester's students who enrolled for MAT111 and MAT112 (male=27 and female=48). The best PLUM model to explain the variation exist in the MAT037 result is Model I which comprised of variables preferences of the students toward the subject and the Mathematics' lecturers also their efforts in learning mathematics. This shows that if the students like Mathematics, they will do extra exercises and always attend the classes. The preferences towards lecturer also influenced the student to like the course. Modell also proved that the student's effort as one of the variables that explained the students' performances in MAT037. The efforts comprised of having consultation with the lecturers, having group discussion and also doing exercises from the assignment and past years questions.